Orsaker till kalvningssvårigheter och dödfödslar hos SLB och SRB - Stolt, Linnea (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2013)
Difficult calvings and stillborn calves are costly for the producer and lowering these frequencies can decrease the costs for the dairy operation. Each calving in the herd is registered by the farmer and stored in a central database. The information is used to monitor the level of calving-difficulties and stillborn calves in the herd and nationally. Monitoring of these registrations is important to detect possible changes. Breeding-value prediction for calving traits is based on the calving information in the database. Heritabilities of calving-traits are low and in the range of 0,01 to 0,08. Calvings are therefore largely affected by environmental factors such as age at first calving, season and herd.